Arbuscular mycorrhizal fungi affect the expression of PxNHX gene family, improve photosynthesis and promote Populus simonii×P. nigra growth under saline-alkali stress - Dong, Fengxin; Wang, Yihan; Tao, Jing; Xu, Tingying; Tang, Ming (Frontiers in Plant Science, 2023)
Saline-alkali stress seriously endangers the normal growth of Populus simonii×P. nigra. Arbuscular mycorrhizal (AM) fungi can enhance the saline-alkali tolerance of plants by establishing a symbiotic relationship with them. In this study, a pot experiment was conducted to simulate a saline-alkali environment where P. simonii×P. nigra were inoculated with Funneliformis mosseae to explore their effects on the saline-alkali tolerance of P. simonii×P. nigra. Our results show that a total of 8 NHX gene family members are identified in P. simonii×P. nigra. F. mosseae regulate the distribution of Na+ by inducing the expression of PxNHXs. The pH value of poplar rhizosphere soil is reduced, result in the promote absorption of Na+ by poplar, that ultimately improved the soil environment. Under saline-alkali stress, F. mosseae improve the chlorophyll fluorescence and photosynthetic parameters of poplar, promote the absorption of water, K+ and Ca2+, thus increase the plant height and fresh weight of aboveground parts, and promote the growth of poplar. Our results provide a theoretical basis for further exploring the application of AM fungi to improve the saline-alkali tolerance of plants.